A note on implicit multifunction theorems - Nghia, T. T. A. (Optimization letters, 2014)
The paper is mainly devoted to the study of implicit multifunction theorems in terms of Fréchet coderivative in Asplund spaces. It sharpens the well-known implicit multifunction theorem of Ledyaev and Zhu (Set Valued Anal., 7, 209–238, 1999 ) as well as many recent publications about this significant area.